All‐Trans‐Retinoic Acid Stimulates Overexpression of Tumor Protein D52 (TPD52, Isoform 3) and Neuronal Differentiation of IMR‐32 Cells. Issue 12 (8th May 2017) - Kotapalli, Sudha Sravanti; Dasari, Chandrashekhar; Duscharla, Divya; Kami Reddy, Karthik Reddy; Kasula, Manjula; Ummanni, Ramesh
ABSTRACT: Tumor protein D52 (TPD52), a proto‐oncogene is overexpressed in a variety of epithelial carcinomas and plays an important role in cell proliferation, migration, and cell death. In the present study we found that the treatment of IMR‐32 neuroblastoma (NB) cells with retinoic acid (RA) stimulates an increase in expression of TPD52. TPD52 expression is detectable after 72 h, can be maintained till differentiation of NB cells suggesting that TPD52 is involved in differentiation. Here, we demonstrate that TPD52 is essential for RA to promote differentiation of NB cells. Our results show that exogenous expression of EGFP‐TPD52 in IMR‐32 cells resulted cell differentiation even without RA. RA by itself and with overexpression of TPD52 can increase the ability of NB cells differentiation. Interestingly, transfection of IMR‐32 cells with a specific small hairpin RNA for efficient knockdown of TPD52 attenuated RA induced NB cells differentiation. Transcriptional and translational level expression of neurotropic (BDNF, NGF, Nestin) and differentiation (β III tubulin, NSE, TH) factors in NB cells with altered TPD52 expression and/or RA treatment confirmed essential function of TPD52 in cellular differentiation. Furthermore, we show that TPD52 protects cells from apoptosis and arrest cell proliferation by varying expression of p27Kip1, activation of Akt and ERK1/2 thus promoting cell differentiation. Additionally, inhibition of STAT3 activation by its specific inhibitor arrested NB cells differentiation by EGFP‐TPD52 overexpression with or without RA. Taken together, our data reveal that TPD52 act through activation of JAK/STAT signaling pathway to undertake NB cells differentiation induced by RA. J. Cell. Biochem. 118: 4358–4369, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Retinoic acid (RA) treatment induces overexpression of TPD52 in IMR‐32 neuroblastoma(NB) cells. TPD52 expression is essential for RA induced differentiation of NB cells. In IMR‐32 cells, TPD52 act through activation of STAT3 to promote NB cells differentiation.